Development of a membrane-based Gi-CASE biosensor assay for profiling compounds at cannabinoid receptors - Scott-Dennis, Morgan; Rafani, Fikri A.; Yi, Yicheng; Perera, Themiya; Harwood, Clare R.; Guba, Wolfgang; Rufer, Arne C.; Grether, Uwe; Veprintsev, Dmitry B.; Sykes, David A. (Frontiers in Pharmacology, 2023)
The cannabinoid receptor (CBR) subtypes 1 (CB1R) and 2 (CB2R), are key components of the endocannabinoid system (ECS), playing a central function in the control of peripheral pain, inflammation, and the immune response, with further roles in the endocrine regulation of food intake and energy balance. So far, few medicines targeting these receptors have reached the clinic, suggesting that a better understanding of the receptor signalling properties of existing tool compounds and clinical candidates may open the door to the development of more effective and safer treatments. Both CB1R and CB2R are Gi protein-coupled but detecting Gi protein signalling activity reliably and reproducibly is difficult because of the inherent variability in live cell-based assays, and the various restrictions faced around the use of radioactive [35S]-GTPγS, one of the favoured technologies for developing higher-throughput membrane-based Gi protein activity assays. Newer more powerful tools have emerged to study GPCR signalling in whole living cells including G protein activation sensors, such as the Gi-CASE biosensors that detect activation and dissociation of the heterotrimeric G protein by monitoring BRET between the α and the βγ subunits. Here, we developed a membrane-based Gi signalling system producing a membrane preparation from stable cell lines overexpressing CB1R or CB2R and the components of the Gi-CASE biosensor. This was possible as the Gi protein is lipidated at the N-terminus of the Gα subunit, and the C-terminus of the Gγ subunit of the G protein. Our membrane-based Gi-CASE nano-BRET system successfully characterised the potency (pEC50) and efficacy (Emax) of CBR- agonists and inverse agonists, in-line with whole-cell Gi-CASE assays and consistent with literature values obtained in various screening formats. This novel, membrane-based assay is applicable to other Gαi-coupled GPCRs, including orphan receptors, thus facilitating convenient real-time higher-throughput measurements of receptor activation.